The role of clusters in the modern economy, their advantages and world experience - Borzenko, O.; Kropova, A. (KU Publ., 2020)
Object: of the article is to study the current state of cluster development in the world, to identify the most successful examples of cluster functioning, as well as the state of cluster development in Ukraine. Accordingly, the subject of the study were clusters. Methods: abstract-logical, system-structural analysis, comparative analysis, grouping and graphic methods were used in the article. Finding: as a result of the study, the state of cluster development in the world was assessed, the best examples of cluster functioning, leading regions and leading countries in this process were identified, and their impact was assessed. The state of cluster development in Ukraine was also taken into account. Conclusions: thus, the economies which use a cluster approach of doing business were analysed. It was found that the most successful in this process is Japan, which has been leading in various rankings for several years. It was also determined that in Ukraine the cluster method of doing business is currently somewhat underdeveloped compared to other countries, and it is at the initial stage of implementation.
Қазіргі заманғы экономикадағы кластерлердің рөлі, олардың артықшылықтары жəне əлемдік тəжірибесі
Роль кластеров в современной экономике, их преимущества и мировой опыт
Keywords: cluster; economy; multinational enterprise; foreign direct investment; region; World Intellectual Property Organization; research and development; innovation; university